FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN - Michelle Rich; Sofia Prima Dewi (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
This study aims to examine whether liquidity, firm size, capital structure, profitability and social responsibility affect firm value. The population is non-primary consumer sector manufacturing companies that have been consistently listed on the Indonesia Stock Exchange for 3 years, namely the 2019-2021 period. The sampling technique used was purposive sampling. The sampels obtained were 21 companies. Data is processed using Eviews 12 SV. This study shows that liquidity and social responsibility do not have a negative effect on firm value, firm size has a negative effect on firm value, capital structure and profitability have a positive effect on firm value.